2021
DOI: 10.3390/ijms22105385
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning in Pancreatic Tissue: Identification of Anatomical Structures, Pancreatic Intraepithelial Neoplasia, and Ductal Adenocarcinoma

Abstract: Identification of pancreatic ductal adenocarcinoma (PDAC) and precursor lesions in histological tissue slides can be challenging and elaborate, especially due to tumor heterogeneity. Thus, supportive tools for the identification of anatomical and pathological tissue structures are desired. Deep learning methods recently emerged, which classify histological structures into image categories with high accuracy. However, to date, only a limited number of classes and patients have been included in histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Three publications focused on AI for the histopathological diagnosis of PDAC. Fu et al (2021) and Naito et al (2021) proposed DL approaches for PDAC diagnosis and segmentation in WSI, while Kriegsmann et al (2021) were the first to utilise DL to automatically identify different anatomical tissue structures and diseases on WSI [ 8 , 47 , 48 ]. AI validation is limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three publications focused on AI for the histopathological diagnosis of PDAC. Fu et al (2021) and Naito et al (2021) proposed DL approaches for PDAC diagnosis and segmentation in WSI, while Kriegsmann et al (2021) were the first to utilise DL to automatically identify different anatomical tissue structures and diseases on WSI [ 8 , 47 , 48 ]. AI validation is limited.…”
Section: Resultsmentioning
confidence: 99%
“…Three publications focused on AI for the histopathological diagnosis of PDAC. [8,47,48]. AI validation is limited.…”
Section: Diagnosismentioning
confidence: 99%
“…This puts at risk the meaningfulness of comparing stage-related outcomes between institutions, to the detriment of patient management, clinical research and cancer registries. Even if, in the not-too-far future, artificial-intelligence-assisted tumour size measurement may overcome current obstacles, study cohorts with correctly measured pancreatic cancers will be invaluable for establishing a robust ground truth [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies ( Cheerla and Gevaert, 2019 ; Peng et al., 2020 ) have demonstrated that WSI data alone, as well as together with genomic data, can achieve a remarkable performance in cancer prognosis prediction. However, most pancreatic cancer-specific studies using WSI data focused on diagnosis, i.e., pancreatic cancer detection and segmentation ( Fu et al., 2021 ; Kriegsmann et al., 2021 ; Le et al, 2019 ). The predictive value of WSI for prognosis purpose has not been rigorously shown in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%